PELATIHAN MEMBUAT VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI INSHOT BAGI GURU SDN 111/I MUARA BULIAN - Eko Kuntarto; Muhammad Sholeh (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
ABSTRACT Learning in target school, namely SDN 111/I Muara Bulian, is generally still conventional and applies the Teacher Center Learning (TCL) model, where teacher is the central figure in the classroom. This is a major problem for the school because conventional learning tends to keep learners from being inspired. However, some teachers in target school are unable to implement innovative learning strategies using technology. One of them is in making audio-visual-based learning media in the form of video. Therefor, a solution was given in the form of training on making learning videos using the Inshot application. This training can make it easier for teachers to make learning videos using their Android. This activity was carried out with a Project Based Learning model and interactive learning methods. Trainers and participants conduct discussions, questions and answers, analyzes, studies, and end with a project. The stages of activity are: (1) preliminary survey; 2) training and guidance; (3) create a project. This training received a very good response from target school, especially teachers who were the trainees. Teachers were becoming more innovative and teaching competencies in this digital era were increasing as evidenced by their success in making interesting learning videos after the training. Keyword: training, learning video, android, Inshot application, teacher